Optimalization of nutrient supply and row space in the growing of annual caraway - Valkovszki, Noémi Júlia; Zámboriné Németh, Éva; Sárosi, Szilvia (Acta Agraria Debreceniensis, 2007)
Concerning the nutrient supply, it was found that the highest crop was produced with the N80K0 treatment (81.38 g m-2). The K application resulted in a decrease in crop yield. The highest crop yield per plant was found in plots with 48 cm row space. The best germination was reached in the plots with 48 cm row space (73%).If the level of K was elevated, the essential oil content increased. The maximum essential oil content was reached by treatment N0K80 (2.6284 ml 100 g sza.-1). The composition of essential oil was influenced both by the nutrient supply and by the growing area. Increasing the row space the ratio of d-carvone decreased. The amount of d-carvone was uniquely increased by use of K. The highest carvone level (66.25%) was identified at the N80+70K80 treatment as an average of row spaces.